Islamic architecture and the prospect of its revival today - Omer, Spahic (Kulliyyah of Architecture and Environmental Design, IIUM, 2011)
This paper discusses the meaning of Islamic architecture and some of its salient characteristics. The discussion is divided into the following sections: (I) What is Islamic architecture?; (2) Islamic architecture as a means, not an end; (3) Two examples: the Islamic house and the mosque; (4) Pragmatism and Islamic architecture today; (5) Towards the revival of Islamic architecture. The paper seeks to enhance the awareness, both of the professionals and general readership, as to the importance of correctly conceptualizing and practicing Islamic architecture. The nature of the paper, along with its content, methodology and conclusions, is conceptual and philosophical, rather than empirical. The paper concludes that Islamic architecture is an architecture that embodies the message of Islam. It both facilitates the Muslims' realization of the Islamic purpose and its divine principles on earth, and promotes a lifestyle generated by such a philosophy and principles. At the core of Islamic architecture lies function with all of its dimensions: corporeal, cerebral and spiritual. The role of the form is an important one too, but only inasmuch as it supplements and enhances function.